MODELING THE CORRECT FORM OF THE DENTAL ARCH IN GIRLS WITH A VERY BROAD FACE DEPENDING ON CEPHALOMETRIC INDICATORS ACCORDING TO STEINER’S OR TWEED’S METHODS AND TOOTH DIMENSIONS - Ryabov, T.V.; Shinkaruk-Dykovytska, М.М.; Pozur, T.P.; Chernysh, A.V.; Prokopenko, O.S.; Vakhovskyi, V.V.; Lysenko, S.A. (World of Medicine and Biology, 2025)
In young Ukrainian women with a physiological bite and a very wide facial type, based on the analysis of the features of teleradiometric indicators according to the Steiner or Tweed methods and computed tomography sizes of the teeth, all possible (18 models each) reliable (p
Keywords: dentistry; teleradiometry; computed tomography dimensions of teeth and dental arches; regression analysis; Ukrainian young women; physiological bite; very wide face type